Applied marketing research - Moutinho, Luiz (Addison-Wesley Pub. Co., 1992)
Provides interesting illustrations and examples of the different kinds of practical problems that are involved in the application of marketing research methodology as an aid to managerial decision making. Thoroughly practical, it forms a complete and concise reference of methodologies and techniques for both the student and the practitioner.